The Role of Lifestyle Intervention in the Prevention and Treatment of Gestational Diabetes - Moholdt, Trine; Hayman, Melanie; Shorakae, Soulmaz; Brown, Wendy J.; Harrison, Cheryce L. (Seminars in Reproductive Medicine, 2020)
Obesity during pregnancy is associated with the development of adverse outcomes, including gestational diabetes mellitus (GDM). GDM is highly associated with obesity and independently increases the risk of both complications during pregnancy and future impaired glycemic control and risk factors for cardiovascular disease for both the mother and child. Despite extensive research evaluating the effectiveness of lifestyle interventions incorporating diet and/or exercise, there remains a lack of definitive consensus on their overall efficacy alone or in combination for both the prevention and treatment of GDM. Combination of diet and physical activity/exercise interventions for GDM prevention demonstrates limited success, whereas exercise-only interventions report of risk reductions ranging from 3 to 49%. Similarly, combination therapy of diet and exercise is the first-line treatment of GDM, with positive effects on maternal weight gain and the prevalence of infants born large-for-gestational age. Yet, there is inconclusive evidence on the effects of diet or exercise as standalone therapies for GDM treatment. In clinical care, women with GDM should be treated with a multidisciplinary approach, starting with lifestyle modification and escalating to pharmacotherapy if needed. Several key knowledge gaps remain, including how lifestyle interventions can be optimized during pregnancy, and whether intervention during preconception is effective for preventing the rising prevalence of GDM.
Keywords: pregnancy; gestational diabetes mellitus; exercise; diet; lifestyle therapy; prevention; treatment